2019
DOI: 10.1063/1.5111548
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength prediction of orthogonal CFRP under high intensity CW laser irradiation

Abstract: Considering the two most important factors, delamination and tensile strength temperature dependence, a tensile strength prediction model for orthogonal carbon fiber reinforced polymer (CFRP) under continuous wave (CW) laser irradiation is proposed. In the prediction model, delamination was judged by the thermal data recorded by a thermal imager. In order to eliminate the influence of heating rate on the tensile strength temperature dependence parameters, a two-sided laser irradiation method was proposed to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the process of laser irradiation, the pressure inside the corner edge increases significantly, and the carbon fibers at the corner edge can change into liquid, thus forming a molten section. Wei et al [ 66 ] irradiated CFRP with a high intensity CW laser and proposed a tensile strength prediction model of orthogonal CFRP under CW laser irradiation. It was found that the prediction model can reflect the decreasing process of tensile strength under laser irradiation, especially in the case of high intensity laser irradiation and high tensile load.…”
Section: Cfrp Laser Processing Optimizationmentioning
confidence: 99%
“…In the process of laser irradiation, the pressure inside the corner edge increases significantly, and the carbon fibers at the corner edge can change into liquid, thus forming a molten section. Wei et al [ 66 ] irradiated CFRP with a high intensity CW laser and proposed a tensile strength prediction model of orthogonal CFRP under CW laser irradiation. It was found that the prediction model can reflect the decreasing process of tensile strength under laser irradiation, especially in the case of high intensity laser irradiation and high tensile load.…”
Section: Cfrp Laser Processing Optimizationmentioning
confidence: 99%
“…[1,2] The theoretical mechanical and physical properties of fiber-reinforced composite materials, such as CFRP, are estimated from the fiber orientation, fiber, matrix properties, and fiber volume fractions, assuming no defect. [3,4] However, it is well-known that the presence of defects can significantly decrease the mechanical and physical properties of CFRP, and some initial defects and the appearance of voids and interlaminar delamination by age deterioration in CFRP are common. [5][6][7][8][9] Therefore, the technique to detect the presence of voids and interlaminar delamination in CFRP and to instantaneously estimate CFRP's actual mechanical and physical properties is industrially applicable.Recently, data science methods, such as machine learning, have attracted attention for their potential to accelerate the design and development process of materials.…”
mentioning
confidence: 99%